ESSENTIAL AND TOXIC MICROELEMENTS IN CLINICAL PRESENTATION OF RECURRENT PYELONEPHRITIS IN CHILDREN - I. A. Mel'nikova; T. A. Nagayeva; I. I. Balasheva (Педиатрическая фармакология)
The study determined content of essential (Zn, Se, Cu) and toxic (Pb, Cd) microelements in blood serum and daily urine in 95 children of 3-15 years of age with recurrent pyelonephritis. It was revealed a statistically significant reduction in the level of essential microelements Se, Cu and Zn in blood serum in comparison with the control group (p<0.05) in the active stage and in the period of decline in activity of pyelonephritis. A statistically significant reduction in Se and Cu urine excretion was registered; at the same time, Zn excretion level was identical to the values in the control group. Study of content of toxic microelements in biological media showed increase in lead concentration in blood serum and urine excretion in children in the period of decline in activity of the disease (p<0.05) and complete clinical laboratory remission (p<0.05) in comparison with the control group. The study did not reveal statistically significant differences in cadmium content in biological media of the examined patients in comparison with the control group. Apparently, deficit of essential microelements in the setting of Pb concentration increase in the body aggravates affection of tubulointerstitial renal tissue resulting in the recurrent course of the disease with brief periods of clinical laboratory remission.